UPAYA PERLINDUNGAN HUKUM BAGI ANAK JALANAN YANG BERPROFESI SEBAGAI PENGAMEN DI DAERAH MEDAN BRAYAN - zulkarnaen zulkarnaen zulkarnaen (jurnal.unprimdn.ac.id, 2018)
The focus of this thesis is on legal protection for street children who work as buskers by the Medan city government in terms of the Law on Child Protection Laws. In this case, the writer used a descriptive Empirical law research method and the analysis that some conclusions are drawn as follows: 1). Generally, the legal protection provided by the Medan city government to street children is a form of assistance if the children are involved or involved in criminal matters. For example, the Medan city government advocates for children who have committed violations or have been victims of physical and psychological violence, etc. However, if the street child is not involved in any legal problem, the Medan city government does not seem to care. This can be proven by the presence of street children at day and night without any supervision from the city government in Medan, in this case, a related section of government. 2). The underlying factors causing them to be street children are the weaknesses of supervision by relevant agencies. Lack of coordination between agencies. 3). Strategic steps taken by the city government are to make a special program on child protection although it cannot be applied by the agency or institution that is given the authority, duties and functions to provide protection to children. This is due to no action or concrete action taken by the agency, namely the Agency for Empowering Women, Children and Family Planning (BPMPAKB) for street children. The research suggest that: 1). Relevant institutions or agencies must supervise and coordinate legal protection that can be given to street children and direct them to leave their profession. 2). increasing the role of non-governmental organizations that are very concerned about street children.